2011
DOI: 10.1007/s00431-011-1525-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in infants with cardiovascular malformations

Abstract: A total of 10.4% of infants who died had a cardiovascular malformation and two-thirds of deaths were due to the malformation or its treatment. Mortality declined due to increasing termination of pregnancy and improved survival after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 19 publications
3
45
0
1
Order By: Relevance
“…[1][2][3][4] Despite advances in pediatric cardiac diagno sis and medical care, congenital heart disease remains the leading cause of perinatal and infant death due to congenital malformations. 5,6 How ever, little information is available about the risk factors, especially modifiable environmental and behavioural factors that may have adverse effects on fetal cardiac development; this lack of information represents a great obstacle in the prevention of congenital heart disease. One earli er study suggested that the proportion of cases attributable to these external factors might be as high as 30% for certain types of congenital heart disease.…”
mentioning
confidence: 99%
“…[1][2][3][4] Despite advances in pediatric cardiac diagno sis and medical care, congenital heart disease remains the leading cause of perinatal and infant death due to congenital malformations. 5,6 How ever, little information is available about the risk factors, especially modifiable environmental and behavioural factors that may have adverse effects on fetal cardiac development; this lack of information represents a great obstacle in the prevention of congenital heart disease. One earli er study suggested that the proportion of cases attributable to these external factors might be as high as 30% for certain types of congenital heart disease.…”
mentioning
confidence: 99%
“…Moreover, the proportion of postoperative deaths due to noncardiac cause increased from 9 % in the first 10 years of the study to 29 % in the second 10 years [3]. These data emphasize the role of additional noncardiac defects for the prognosis of children with CHD since these subjects with multiple and complex defects represent about one third of all CHD and can be considered one of the next challenges for pediatric cardiologists and cardiac surgeons [1,2].…”
mentioning
confidence: 69%
“…The authors reported that the deaths were not related to cardiovascular malformations in 33 % of all patients: in 57 % of infants with additional chromosomal or genetic abnormalities, in 76 % of infants with major noncardiac malformations, and in only 16 % of infants with isolated cardiac defects [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations